A Comparison of Health Achievements in Rwanda and Burundi - Iyer, Hari S. (FXB Harvard School of Public Health, 2021)
Strong primary health care systems are essential for implementing universal health coverage and fulfilling health rights entitlements, but disagreement exists over how best to create them. Comparing countries with similar histories, lifestyle practices, and geography but divergent health outcomes can yield insights into possible mechanisms for improvement. Rwanda and Burundi are two such countries. Both faced protracted periods of violence in the 1990s, leading to significant societal upheaval. In subsequent years, Rwanda’s improvement in health has been far greater than Burundi’s. To understand how this divergence occurred, we studied trends in life expectancy following the periods of instability in both countries, as well as the health policies implemented after these conflicts. We used the World Bank’s World Development Indicators to assess trends in life expectancy in the two countries and then evaluated health policy reforms using Walt and Gilson’s framework. Following both countries’ implementation of health sector policies in 2005, we found a statistically significant increase in life expectancy in Rwanda after adjusting for GDP per capita (14.7 years, 95% CI: 11.4–18.0), relative to Burundi (4.6 years, 95% CI: 1.8–7.5). Strong public sector leadership, investments in health information systems, equity-driven policies, and the use of foreign aid to invest in local capacity helped Rwanda achieve greater health gains compared to Burundi.